2017
DOI: 10.1021/acs.analchem.7b02226
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of Vesicle Opening during Analysis with Vesicle Impact Electrochemical Cytometry

Abstract: Vesicle impact electrochemical cytometry (VIEC) has been used to quantify the vesicular transmitter content in mammalian vesicles. In the present study, we studied the mechanism of VIEC by quantifying the catecholamine content in single vesicles isolated from pheochromocytoma (PC12) cells. These vesicles contain about one tenth of the catecholamine compared with adrenal chromaffin vesicles. The existence of a prespike foot for many events suggests the formation of an initial transiently stable pore at the begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 49 publications
8
59
1
Order By: Relevance
“…[12][13][14]16,17 According to Ewing and co-workers, the so-called vesicle impact electrochemical amperometry is mainly driven by an electroporation process of the vesicle membrane on polarized carbon UMEs which leads to the vesicle rupture and the electrolysis of its content. [18][19][20][21] Vesicle membrane opening by electroporation is strongly dependent on lipid membrane properties, liposome content, vesicle size, temperature, electrode potential, the nature of the electrode and probably the concentration of redox species inside and outside the liposome. [18][19][20][21][22] For example, to observe the current spikes corresponding to the oxidation of ferrocyanide encapsulated inside phospholipid vesicles when they collide with a Pt UME, the presence of an appropriate concentration of surfactant in solution is required.…”
Section: /19mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14]16,17 According to Ewing and co-workers, the so-called vesicle impact electrochemical amperometry is mainly driven by an electroporation process of the vesicle membrane on polarized carbon UMEs which leads to the vesicle rupture and the electrolysis of its content. [18][19][20][21] Vesicle membrane opening by electroporation is strongly dependent on lipid membrane properties, liposome content, vesicle size, temperature, electrode potential, the nature of the electrode and probably the concentration of redox species inside and outside the liposome. [18][19][20][21][22] For example, to observe the current spikes corresponding to the oxidation of ferrocyanide encapsulated inside phospholipid vesicles when they collide with a Pt UME, the presence of an appropriate concentration of surfactant in solution is required.…”
Section: /19mentioning
confidence: 99%
“…[18][19][20][21] Vesicle membrane opening by electroporation is strongly dependent on lipid membrane properties, liposome content, vesicle size, temperature, electrode potential, the nature of the electrode and probably the concentration of redox species inside and outside the liposome. [18][19][20][21][22] For example, to observe the current spikes corresponding to the oxidation of ferrocyanide encapsulated inside phospholipid vesicles when they collide with a Pt UME, the presence of an appropriate concentration of surfactant in solution is required. 14 In the absence of surfactant, we found that collision and adhesion of vesicles at the Pt UME does not allow the electrolysis of their ferrocyanide content.…”
Section: /19mentioning
confidence: 99%
“…Although we chose nanoparticle collision experiments as the system of interest for this study, the basic concepts of filters discussed throughout this report are generally applicable to all single‐entity experiments. For example, the instrument bandwidth could affect the measurement of the shortest lifetimes associated with single‐nucleotide base‐flipping states in a single DNA molecule, or the timescale for electrochemical conversion of neurotransmitters in vesicles …”
Section: Introductionmentioning
confidence: 99%
“…They compared the results from intracellular vesicle electrochemical cytometry with those from chemically stimulated exocytosis. [90] Furthermore, they found that the probability of vesicle rupture was related to vesicle size, temperature, and preexposure to drugs that manipulate vesicular content. [89] Recently, pretransient or prespike feet in events under certain conditions were observed, thus supporting the mechanism of electroporation for pore opening.…”
Section: Application To Intracellular Vesicle Analysismentioning
confidence: 99%
“…[89] Recently, pretransient or prespike feet in events under certain conditions were observed, thus supporting the mechanism of electroporation for pore opening. [90] Furthermore, they found that the probability of vesicle rupture was related to vesicle size, temperature, and preexposure to drugs that manipulate vesicular content. A recent study showed closely agreeing catecholamine distributions obtained by measuring the vesicular catecholamine content in extracted and intracellular vesicles by employing disk and nanotip conical microelectrodes.…”
Section: Application To Intracellular Vesicle Analysismentioning
confidence: 99%